New towns in Poland - Sokołowski, Dariusz (Bulletin of Geography. Socio-economic Series, 2014)
Over the last three decades, more than a hundred new towns have emerged in Poland. The paper concerns the characteristics of these towns. It also addresses transformation of the settlement pattern caused by the change of the towns’ formal-legal status. The paper also verifies the hypotheses aimed at identifying the factors that contribute to the creation of new towns.